Significantly Lower Saliva Secretion in Females With Gastroesophageal Reflux Disease and Healthy Subjects Than in Males - Momma, Eri; Koeda, Mai; Hoshikawa, Yoshimasa; Tanabe, Tomohide; Hoshino, Shintaro; Kawami, Noriyuki; Iwakiri, Katsuhiko (Curēus (Palo Alto, CA), 2023)
Saliva secretion in healthy subjects is lower in females than in males. The present study investigated sex differences in saliva secretion in patients with gastroesophageal reflux disease (GERD) and healthy controls. This case-control study included 39 (male/female: 16/23) with non-erosive reflux disease (NERD), 49 (25/24) patients with mild reflux esophagitis, 45 (23/22) with severe reflux esophagitis (A1), and 46 (24/22) healthy controls. Saliva secretion was examined as follows: before endoscopy, patients chewed sugar-free gum for three minutes, and the amount and pH of saliva before and after acid loading as an index of acid-buffering capacity were evaluated. The relationships between saliva secretion and body mass index, height, and weight were also examined. The amount of saliva secreted was significantly lower in females than in males in all four groups (NERD, mild reflux esophagitis, severe reflux esophagitis, and healthy controls). Salivary pH and acid-buffering capacity were similar in all groups. The amount of saliva secreted positively correlated with height and body weight, albeit more strongly with height. A sex difference in saliva secretion exists in GERD patients, similar to healthy controls. Saliva secretion was significantly lower in female GERD patients than in male GERD patients.